MICROCREDIT, FINANCIAL INCLUSION AND WOMEN'S ECONOMIC AUTONOMY: AN INSTITUTIONAL ANALYSIS BASED ON THE ITAÚ UNIBANCO CASE (REMUNOM, 2026)
This study analyzes the relationship between microcredit, financial inclusion, and women's economic autonomy through the examination of institutional strategies developed by Itaú Unibanco aimed at supporting low-income female entrepreneurship. The research adopts a qualitative, descriptive, and exploratory approach, combining a literature review with a case study based on documentary analysis of institutional reports and materials. The findings indicate that, in the analyzed context, microcredit is embedded in a broader strategy that integrates credit provision with training, networking, and institutional support. These initiatives are presented as mechanisms for strengthening women’s economic participation and productive inclusion. However, both the literature and the analyzed data suggest that their effects depend on specific social, institutional, and gender-related conditions. The study highlights the multifaceted nature of microcredit and emphasizes the importance of considering its limitations and mediating factors, rather than assuming automatic impacts on economic autonomy and poverty reduction.